2018
DOI: 10.1159/000487980
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Influences BRL-3A Cell Lipid Metabolism via the AMPK Signalling Pathway

Abstract: Background/Aims: Acetic acid (AcOH), a short-chain fatty acid, is reported to have some beneficial effects on metabolism. Therefore, the aim of this study was to investigate the regulatory mechanism of acetic acid on hepatic lipid metabolism in BRL-3A cells. Methods: We cultured and treated BRL-3A cells with different concentrations of sodium acetate (neutralized acetic acid) and BML-275 (an AMPKα inhibitor). The total lipid droplet area was measured by oil red O staining, and the triglyceride content was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…These investigators found that acetate activation of the AMPKα signaling pathway led to increased lipid oxidation and decreased lipid synthesis. Later studies using a rat liver cell line confirmed that acetate administration increased AMPKα phosphorylation (Li et al, 2018). These findings make physiological sense if systemic acetate, like ketone bodies, signals mobilization of energy reserves where lipolysis and fatty acid β-oxidation are central.…”
Section: Acetate Acss2 and Metabolic Regulation Through Ampkmentioning
confidence: 89%
“…These investigators found that acetate activation of the AMPKα signaling pathway led to increased lipid oxidation and decreased lipid synthesis. Later studies using a rat liver cell line confirmed that acetate administration increased AMPKα phosphorylation (Li et al, 2018). These findings make physiological sense if systemic acetate, like ketone bodies, signals mobilization of energy reserves where lipolysis and fatty acid β-oxidation are central.…”
Section: Acetate Acss2 and Metabolic Regulation Through Ampkmentioning
confidence: 89%
“…Western blot analysis of cells was performed as described previously . MAC‐T cells were treated with 1 μg/mL LPS for 9 hours before being exposed to 50 μM PI3K inhibitor (LY294002) for 1 hour and then 16 μM NaB for another 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…As an important energy source for the gastrointestinal tract, sodium butyrate (NaB) inhibits intestinal pathogenic bacteria and maintains gastrointestinal homeostasis . A previous study revealed that butyrate can suppress the inflammatory response and that this suppression is associated with modulating the phosphatidylinositol 3‐kinase (PI3K)/AKT pathway and the abolition of lipopolysaccharide (LPS)‐induced cytokine expression . Butyric acid supports mitochondrial function, stimulates oxidative phosphorylation and fatty acid oxidation, upregulates physiological stress pathways, and is critical for colonocyte mitochondrial function in germ‐free mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, certain organic acids such as acetic acid (AA) and its common solution "vinegar" are food additives permitted in feed and drinking water of poultry (acidifiers) anticipating accelerated nutrients digestion, absorption and metabolism through certain mechanisms (Ndelekwute, Unah, & Udoh, 2019). Acetic acid is suggested to reduce liver fat by activating the AMPK pathway (Li et al, 2018;Petsiou, Mitrou, Raptis, & Dimitriadis, 2014) and alleviates the inflammatory response and liver injury by increasing the expression of TRIM40 gene (Yang et al, 2019). Therefore, we hypothesized that based on the theoretical knowledge at hand, concomitant feeding of Satureja khuzistanica essential oils (SkEO) in graded levels and dietary AA may exert significant facilitating effects on lipids metabolism in broiler liver.…”
mentioning
confidence: 99%